Effects of sexual orientation-based bullying on feelings of loneliness and sleeping difficulty among Brazilian middle school students - Rafael Tavares Jomar; Vitor Augusto de Oliveira Fonseca; Dandara de Oliveira Ramos (Elsevier, 2021)
Objective: To investigate the extent to which sexual orientation-based bullying relates to self-reported feelings of loneliness and sleeping difficulty among Brazilian middle school students. Method: This is a cross-sectional study using data from the 2015 PeNSE (Pesquisa Nacional de Saúde do Escolar), a survey designed to monitor the health of children and adolescents enrolled in the ninth grade in public and private Brazilian schools. Multiple linear regressions stratified by sex were used on a sample of 101,646 students, considering as reference students who had not experienced bullying, as well as students who had experienced other causes of bullying; a significance level of p < 0.05 was accepted. Results: When the reference group was composed of students who had not experienced bullying, the associations between sexual orientation-based bullying and feelings of loneliness and between sexual orientation-based bullying and sleeping difficulty were positive (p < 0.05) for both male and female students, with magnitudes about twice as large as those found among those who reported having experienced other cause s of bullying. However, when the reference group was composed of students who had experienced other causes of bullying, only the association between sexual orientation-based bullying and feelings of loneliness was positive (p < 0.05) for both male and female students. Conclusion: This study highlights that sexual orientation-based bullying is a predictor of feelings of loneliness.